Regulating Transboundary Water Resources and Hydraulic Infrastructure in Central Asia - Mukasheva Anor Abaikhankyzy; Narzullaev Olim Kholmamatovich; Teleuyev Galym Baygazyevich; Bekturganov Abdimanap Elikbaevich; Tanatbaeva Zhaidary Ergalievna (Contrarius Indonesia, 2026)
Despite the formal recognition of international water law principles, Central Asian states have not effectively incorporated these norms into enforceable domestic regulations governing the Amu Darya and Syr Darya basins. This study aims to examine the extent to which international legal standards governing transboundary water management are incorporated into domestic regulatory regimes and to evaluate the capacity of existing legal frameworks to address emerging cross border risks related to water allocation and hydrotechnical safety. The research employs a doctrinal and comparative legal approach by interpreting treaty obligations and systematically analysing national legislation and institutional arrangements in selected Central Asian jurisdictions. The findings identify three principal issues. First, states formally recognise the principle of equitable utilisation but fail to establish precise allocation rules and effective enforcement mechanisms. Second, national authorities regulate hydrotechnical safety primarily within domestic legal systems without developing binding cross border supervision mechanisms. Third, fragmented institutional mandates weaken coordinated compliance with transboundary obligations. The study concludes that institutional fragmentation rather than normative scarcity constitutes the principal regulatory challenge, and that sustainable regional water governance requires integrated basin level institutions, harmonised safety standards, and enforceable cooperative mechanisms among riparian states.